Od podatkov do informacij za rehabilitacijo prihodnosti - Vidmar, Gaj (Rehabilitacija (Ljubljana), 2009)
The paper strings out some personal thoughts on possibilities for development in all the phases of handling data in rehabilitation and related fields and practices, grounded in words of acknowledged thinkers and references to established sources. The technology of today offers sufficient possibilities for markedly improving collection, analysis, display and interpretation of data, so I see the forthcomming decade mainly as the period of making these possibilities come true by means of expanding and increasing the knowledge of everyone involved. The conceptual basis for all this has long been around, namely in the form of the universal science of data - statistics. I wish statistical thinking and application of contemporary statistical knowledge, backed up by commitment to the use of information technology for the benifit of the rehabilitees and the general public, throughout all phases of rehabilitation - from planning interventions and research through appraising outcomes and research achievements to managerial decisions and healthcare policy - were not only an utopian dream of an individual, but rather became one of the goals of the whole education system, one of the principles of work organisation of the whole healthcare system, and one of personal values of everyone working in the field of rehabilitation.
Keywords: informacijski sistemi; podatki; rehabilitacija; vocational rehabilitation; informacijska družba; upravljanje znanja